EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN PRESTASI BELAJAR IPAS KELAS V DI SD NEGERI NGEBEL - Aa Rahmawati; Setyo Eko Atmojo (STKIP Subang, 2026)
This study aims to determine the effectiveness of using Canva-based learning media on students’ academic achievement in the IPAS subject at Ngebel Public Elementary School. The background of this study is based on students’ low academic achievement and the lack of engaging and interactive learning media in the learning process. Therefore, there is a need for innovative learning media capable of improving students’ academic achievement. This study is a quantitative research using an experimental design with a quasi-experimental design in the form of a nonequivalent control group design. Data collection instruments used tests (pretest and posttest). Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using an independent samples t-test with the assistance of SPSS. The research results indicate that the significance value is 0.001 < 0.05, so H_a is accepted and H_o is rejected. Thus, there is a significant difference between the average learning outcomes of students in the control class and the experimental class after the treatment was administered. This indicates that the use of Canva-based learning media has a significant effect on improving student learning achievement in the IPAS subject at Ngebel State Elementary School. Based on these research results, it can be concluded that Canva-based learning media is effective in the learning process because it can improve students’ learning achievement. Therefore, it is recommended that educators utilize Canva-based learning media as an alternative to create more interactive learning experiences.